ANALYSIS OF FACTORS AFFECTING COLLATERAL VALUE (Study at Bank Perekonomian Rakyat Nusantara Bona Pasogit) - Fitriana; Elisabeth Siahaan; Rudy Siahaan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study analyzes the factors influencing collateral value at Bank Perekonomian Rakyat Nusantara Bona Pasogit (BPR NBP), a rural bank that plays an important role in providing credit to micro, small, and medium enterprises. The research was conducted at four BPR NBP branches located in North Sumatra and West Java, using 95 collateral data collected from 2022 to 2024. A quantitative approach was employed through multiple linear regression and Pearson correlation analysis to examine the effect of physical, legal, and locational variables on collateral value. The analyzed variables include land area, frontage width, road construction, land shape, land ownership legality, distance to the Central Business District, distance to main roads, and distance to government markets. The results indicate that all independent variables simultaneously have a significant effect on collateral value. Partially, land area and land shape positively and significantly influence collateral value, while land legality shows an unexpected negative effect. These findings highlight the importance of adopting a multivariate approach in collateral valuation to improve appraisal accuracy, strengthen credit risk management, and support more objective lending decisions in rural banking institutions.